The 27th Amendment and its Impact on the Strength of Democracy and Federalism in Pakistan - Mehreen Yaseen; Sadaf Ghayoor; Rabia Iqbal; Jaffar Khan; Iqra Zafar (Indus Journal of Social Sciences, 2025)
The paper provides an in-depth analysis of the 27 th Constitutional Amendment of Pakistan that took place in 2025 and its implications on the principles of a democratic government and the federal system. Article 51(5) and 106(2) are amended by the amendment, which is a procedural reform, with substantive (although mainly indirect) effects on electoral legitimacy and provincial representation, primarily aimed at making it easier to delimit constituencies, following the 2025 Digital Census. By applying a two-pronged methodology, i.e. a legal analysis and a comparative policy analysis, the paper places the amendment in the context of apportionment and unequal distribution of resources between Pakistani inter-provincial units that Pakistan has been facing. As practices have shown, procedural, the amendment strengthens democratic values by requiring the drawing of electoral boundaries based on the present demographic realities, thus maintaining the objectivity of the principle of one person one vote. Such a realignment is specifically crucial in responding to the high urbanization and demographic changes that are witnessed in some provinces like Sindh and Khyber Pakhtunkhwa. The resultant correspondence of constituency boundary to the current population statistics is a decisive move towards eliminating voter inequity. Through federalist view, the amendment revitalizes the federalist agreement that required that the distribution of seats in the National Assembly should be based on the most recent population estimates of the federating units. Working openly on the basis of census-derived data, the state, in addition to strengthening the legitimacy of the federal arrangement, maintains mutual trust between the central government and the provincial governments. This recalibration of the procedure fortifies the formal mechanisms in which the federal bargain is based upon. The research also finds however, that the effectiveness of the amendment is limited to the procedural domain; it does not involve substantive changes to the electoral systems or structural reforms to support the long-term democratic consolidation or fiscal federalism. Therefore, although the amendment is an essential administrative trick, it does not amount to a massive restructuring of the constitution.